Entrepreneurial Behavior of Vegetable Growers and Determinants: A Study in Ferozepur District of Punjab, India - Satvik Chopra; Rakesh Rathore (Archives of Current Research International, 2024)
The present study attempted to analyze the entrepreneurial behavior of vegetable growers and factors influencing entrepreneurial behavior of vegetable growers in Ferozepur district of Punjab during 2024. A multistage simple random sampling technique was used for the selection of the respondents. During the study total 120 vegetable growers were selected for the present study. Mean, frequency, percent, one sample t-test were used for the analysis of the collected data. The results of the study revealed that majority of the farmers (35 per cent) had experience of 5-10 years in vegetables cultivation. Farmers cultivated vegetables to avoid risk (4.26) and adopt recommended package of practices for vegetables cultivation (3.72). Access to reliable market and buyers greatly affect entrepreneurial behavior (4.57) were reported important constraint. Income enhancements through vegetable cultivation are the important motivation factor to the farmers. Favorable supportive policies in this regard may enrich the entrepreneurial ecosystem among the vegetable growers.